Trophy hunt (Joe Pickett novel, 5,, 2005)
Shaken by the brutal killing of a wild moose, game warden Joe Pickett becomes increasingly alarmed when a herd of cattle, and then two people, are murdered by the same perpetrator.

Free fire (Joe Pickett novel, 7,, 2008)
When four environmental activists employed by Yellowstone Park are murdered in an isolated area, the Wyoming governor sends outspoken Joe Pickett, from the state's game and fish department, to investigate.

Vicious circle (Joe Pickett, 17,, 2017)
The plane circled in the dark. Joe Pickett could just make out down below a figure in the snow and timber, and then three other figures closing in. There was nothing he could do about it. And Joe knew that he might be their next target.

Open season (Joe Pickett novel, 1,, 2002)
As Wyoming game warden Joe Pickett races against time to save an endangered species, he finds himself plunged into a deadly mystery that soon threatens his family and the life he loves.

Winterkill (Joe Pickett novel, 3,, 2004)
Joe Pickett finds himself at the center of a confrontation between a special investigative team and a group of government-hating survivalists campedout on federal land. With the help of a mysterious stranger, Joe lays his life on the line to protect an innocent girl before a wave of violence surges over the Bighorn Mountains.

Out of range (Joe Pickett, 5,, 2008)
Discovering that a friend and fellow game warden has committed suicide, Joe Pickett is assigned to the man's district in Jackson, Wyoming, and becomes a pawn in a struggle between environmental extremists and their powerful adversaries.

Savage run (Joe Pickett novel, 2,, 2016)
Wyoming game warden Joe Pickett heads for the forests of Twelve Sleep County to investigate a massive explosion that may have killed an environmental activist and uncovers evidence of a deadly conspiracy.

In plain sight (Joe Pickett novel, 6,, 2008)
Ranch owner and matriarch Opal Scarlett has vanished under suspicious circumstances during a bitter struggle between her sons for control of her million-dollar empire. Joe Pickett is convinced one of them have done her in, and when he becomes the victim of a series of wicked and increasingly violent pranks, Joe wonders if what's happening has less to do with Opal's disappearance than with the darkest chapters of his own past. Whoever is after him has a vicious debt to collect, and wants Joe to pay ... and pay dearly.

Off the grid (Joe Pickett novel, 16,, 2016)
When an elite special ops team recruits him to help defeat a domestic terror cell in Wyoming's Red Desert in exchange for expunging his criminal record, Nate Romanowski, assisted by Joe Pickett, discovers a sinister agenda behind the operation.

Stone cold (Joe Pickett novel, 14,, 2014)
Investigating allegations about a hit man who lives a life of wealth and secrecy on a remote Wyoming ranch, troubleshooter Joe Pickett discovers two men at the ranch including a ruthless killer and a disturbing person from his past.

Endangered (Joe Pickett, 15,, 2015)
When Wyoming game warden Joe Pickett's eighteen-year-old ward runs away with Dallas Cates and then is found in a ditch barely alive, Joe believes Cates is responsible. But Cates claims that she ran away from him too and evidence points to another man. Joe is determined to find the truth, even if it kills him. --Provided by publisher.

Storm watch (Joe Pickett, 23,, 2023)
When a prominent University of Wyoming professor goes missing, authorities are stumped. That is, until Joe Pickett makes two surprising discoveries while hunting down a wounded elk on his district as an epic spring storm descends upon him. First, he finds the professor's vehicle parked on a remote mountainside. Then Joe finds the professor's frozen and mutilated body. When he attempts to learn more, his investigation is obstructed by federal agents, extremists, and Governor Colter Allen. Nate Romanowski is rebuilding his falconry company--and financing this through crypto mining with the assistance of Geronimo Jones. He's then approached by a shadowy group of local militant activists that is gaining in power and influence, and demanding that Wyoming join other western states and secede from the union--by force, if necessary. They ask Nate to throw in with them, but he's wary. Should he trust them, or is he being set up? As a storm of peril gathers around them, Joe and Nate confront it in different ways--and maybe, for the first time, on opposite sides.

Breaking point (Joe Pickett novel, 13,, 2016)
Joe Pickett investigates the disappearance of a local businessman, who recently had his intended retirement property declared wetlands and is suspected in the murder of two EPA employees.

The disappeared (Joe Pickett, 18,, 2018)
Wyoming's new governor isn't sure what to make of Joe Pickett, but he has a job for him that is extremely delicate. A prominent female British executive never came home from the high-end guest ranch she was visiting, and the British Embassy is pressing hard. Pickett knows that happens sometimes--these ranches are stocked with handsome young cowboys, and "ranch romances" aren't uncommon. But no sign of her months after she vanished? That suggests something else. At the same time, his friend Nate Romanowski has asked Joe to intervene with the feds on behalf of falconers who can no longer hunt with eagles even though their permits are in order. Who is blocking the falconers and why? The more he investigates both cases, the more someone wants him to go away. Is it because of the missing woman or because he's become Nate's advocate? Or are they somehow connected? The answers, when they come, will be even worse than he'd imagined.

Blood trail (Joe Pickett, 8,, 2008)
Joe Pickett is governor Rulon's instinctive choice to track the gruesome murder of a hunter at the start of the elk season in the Rockies. The community is fearful and wonders whether the killer is a psychopath or a deranged anti-hunting activist.

Cold wind (Joe Pickett novel, 11,, 2011)
When Earl Alden is found dead, dangling from a wind turbine, it's his wife, Missy, who is arrested. Unfortunately for Joe Pickett, Missy is his mother-in- law, a woman he dislikes heartily, and now he doesn't know what to do --especially when the early signs point to her being guilty as sin. But then things happen to make Joe wonder: Is Earl's death what it appears to be? Is Missy being set up?

Shots fired: stories from Joe Pickett Country (Joe Pickett novel, 15,, 2014)
Over the course of eighteen books, C. J. Box has been consistently hailed for his brilliant storytelling and extraordinary skills at creating character, suspense, and a deep sense of place. All of those strengths are in the ten riveting stories-three of them never before published-that make up 'Shots Fired.' In 'One-Car Bridge,' one of four Joe Pickett stories, Pickett goes up against a 'just plain mean' landowner, with disastrous results, and in 'Shots Fired,' his investigation into the radio call referred to in the title nearly ends up being the last thing he ever does. In 'Pirates of Yellowstone,' two Eastern European tough guys find out what it means to be strangers in a strange land, and in 'Le Sauvage Noble,' the stranger is a Lakota in Paris who enjoys playing the 'noble savage' for the French women-until he meets Sophie. Then he discovers what 'savage' really means. 'Shots Fired' is proof once again why 'Box is a force to be reckoned with' ('The Providence Journal-Bulletin').
One-car bridge , Pirates of Yellowstone , The end of Jim and Ezra , The Master falconer , Every day is a good day on the river , Pronghorns of the Third Reich , Dull knife , Le Sauvage Nobel (The Noble Savage) , Blood knot , Shots fired: A requiem for Ander Esti.

Three-inch teeth (Joe Pickett, 24,, 2024)
A rogue grizzly bear has gone on a rampage--killing, among others, the potential fiancé of Joe's daughter. At the same time, Dallas Cates, who Joe helped lock up years ago, is released from prison with a special list tattooed on his skin. He wants revenge on the people who sent him away: the six people he blames for the deaths of his entire family and the loss of his reputation and property. Using the grizzly attacks as cover, Cates sets out to methodically check off his list. The problem is, both Nate Romanowski and Joe Pickett are on it.

Below zero (Joe Pickett, ,, 2009)
Shocked by a phone message that his believed-dead foster daughter may still be alive, Wyoming game warden Joe Pickett becomes increasingly suspicious when subsequent calls are placed from locations where serious crimes have occurred.

Joe Pickett: season 1 (Paramount, 2023)
Based on the best-selling book series from CJ Box, Joe Pickett is the new game warden of a town as beautiful and charming as it is corrupt and dangerous. When a poacher turns up brutally murdered, Joe decides to investigate it to keep his wife and young daughters safe. This sets off a chain of events that uncovers lies and deceit from within the community, putting Joe and his family in mortal danger. The three-disc DVD set includes every episode from season one plus exclusive deleted scenes!
Disc 1: A monster at the gate , Circling vultures , Joey, get your gun , Special features ; Disc 2: A consipiracy of ravens , Live and look like a million , Shoot, shovel, and shut up , The most hated ma in twelve step , Special features ; Disc 3: The killing fields , Endangered , Open season , Special features.